Effects of organic salts on the rate of alkaline hydrolysis of phthalimide in the presence ofcationic micelles - Khan, M. Niyaz; Ahmad, Faujan B. H. (Kluwer Academic Publishers, Dordrecht and Akadémiai Kiadó, Budapest, 2001)
Pseudo-first order rate constants (kobs) for alkaline hydrolysis of phthalimide (PTH), obtained at constant concentration of cetyltrimethylammonium bromide (CTABr) and 35°C, vary with the concentration of organic salts ([MX]) according to the relationship: kobs = (k0 + θ K [MX])/(1 + K [MX]) where θ and K are empirical parameters. The values of K at 0.01 M CTABr are nearly 2 times larger than the corresponding K values at 0.02 M CTABr for sodium benzoate, disodium phthalate and disodium isophthalate.